FIRST EYE CATARACT SURGERY AND HOSPITALISATION FOR A FALL. (7th October 2012) - Meuleners, L; Ng, J; Morlet, N; Fraser, M
Abstract : Background: With an increasing ageing population, the burden from both visual impairment and falls is expected to increase substantially. Cataract surgery is known to improve vision as well as enhancing quality of life, activity levels and confidence, however, little is known about the impact of cataract surgery on falls. Aims/ Objectives/ Purpose: To assess the association between first eye cataract surgery and hospitalisation from injuries due to a fall in older adults at the population level. Methods: A retrospective population-based study was undertaken using the Western Australian Hospital Morbidity Data System and Western Australian mortality data between 2004 and 2008. Results/ Outcomes: Of the 15, 295 patients who underwent cataract surgery in one eye only, 600 patients (3.92%) were involved in 625 hospital admissions from injuries due to a fall, either one year before (n=273) or one year after (n=352) first eye cataract surgery. Thirty percent of these hospitalisations were for femoral neck fractures. Poisson generalised estimating equations confirmed a significant increase of 27% (adjusted risk ratio 1.27, 95% CI 1.04 to 1.56; p=0.02) in hospitalisation from injuries due to a fall one year after first eye cataract surgery. Significance/ Contribution to the field: First eye cataract surgery was associated with an increase in hospital admission from injuries due to a fall in the year after, compared to the year before cataract surgery. Further research is needed to determine the underlying causes and reasons.